Family communication and coping among racial‐ethnic minority cancer patients: A systematic review. (29th October 2021) - Huang, Yu‐Ju; Acquati, Chiara; Cheung, Monit
Abstract: The ability to actively cope with cancer has been extensively associated with better patient‐reported outcomes (PROs). This systematic review aims to synthesise the available literature assessing the experience of cancer patients from racial‐ethnic minoritised groups. Given the role of sociocontextual factors, greater emphasis was placed on the relationship between family communication and cancer patients' coping within the three largest racial‐ethnic minority groups in the United States. Five databases (CINAHL, MEDLINE, PsycINFO, PubMed, Web of Science) were used to search for peer‐reviewed empirical studies published between 2008 and 2021, investigating family communication patterns, coping, and well‐being among Black/African American, Asian, and Hispanic/Latinx cancer survivors. Short reports, chapters, abstracts/summaries, systematic reviews, and conference proceedings were excluded. This review was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Statement (PRISMA). The Criteria for Critically Appraising Systematic Reviews and Meta‐Analyses were used to assess the quality and risk of bias in the included studies. The synthesis process focused on study aims, methods, measures of interests, sample characteristics, data analysis, and study findings. A total of 117 articles were identified, of which 9 met the inclusion criteria. The selected articles were cross‐sectional, implementing both quantitative and qualitative designs. Studies included breast, prostate, and mixed cancer types. Sample sizes of quantitative studies ranged from 64 to 338 respondents, while qualitative studies' samples ranged between 9 and 43 participants. Family communication and coping styles varied across minoritised groups, with open family communication contributing to effective individual and family coping. However, empirical evidence about the nature and contribution of family communication to the coping process is sparse. Future research is needed to increase knowledge and psychosocial assessment techniques and interventions targeting family communication and coping among minority communities.